Business Process Reengineering Approval Services For Spatial Use Activities - Surya Ningrat Datunsolang; Richi Firmansyah Gobel (Borong Newinera Publisher, 2023)
This Business Process Reengineering aims to redesign the business process of the Land Use Utilization Compliance Approval Service (PKKPR) in North Bolaang Mongondow Regency. The method used involves the following stages: 1) Engineering Preparation; 2) As-Is Process analysis; 3) To-Be Process Engineering; 4) Analysis of modified time base value added. After conducting the analysis of the 'To-be' Business Process, there has been an improvement in service value, which can be measured by: 1) An increase in VAR by 18.96%; 2) A significant increase in Business Process Effectiveness, reaching 100%, which can be described as Highly Effective; 3) A decrease in the complexity score of the business process to 2040, indicating that the business process has become less complex.